A crack-resistant welding material for a main frame of a wind turbine nacelle chassis and a preparation method thereof
Through the mixed preparation method of alloy powder, composite nano silica and additives, the problem of prone to solidification cracks during welding is solved, and welding materials with high toughness, wear resistance, corrosion resistance and crack resistance are prepared to meet the wear repair needs of wind turbines.
Patent Information
- Application Number
- CN202411183610.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-08-27
AI Technical Summary
Existing welding materials are prone to solidification cracks during welding, resulting in unstable welding and cannot meet the wear and repair needs of the main frame of the wind turbine cabin.
Using the mixed preparation method of alloy powder, composite nano silica and additives, welding materials with high toughness, wear resistance, corrosion resistance and crack resistance are prepared by ultrasonic stirring and electroplating.
It improves the welding performance of the welding material, ensures the densification of the weld structure, enhances the crack resistance and wear resistance of the welding material, and meets the wear repair needs of wind turbines.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, in particular to an anti-cracking welding material for a main frame of a wind turbine nacelle chassis and a preparation method thereof. Background Art
[0002] With the massive consumption of traditional fossil energy, wind power generation, as one of the clean energy sources, has huge room for development. With the increasing market demand for wind power efficiency, how to ensure the safe and efficient operation of various wind turbine components has become a hot research topic. The nacelle, chassis, and main frame are the main load-bearing components of wind turbines. In practice, they bear a variety of complex loads. Therefore, the quality of each component is closely related to the quality and safety reliability of wind turbines.
[0003] In practical applications, because wind turbines face a more changeable outdoor environment, wear and repair are existing hot issues. Currently, technical methods such as surfacing, spraying, laser and plasma arc cladding are commonly used for wear repair. In the welding process, flux-cored wire welding materials are commonly used welding materials. However, some welding materials on the market have high sensitivity to welding solidification cracks and are prone to cracking during the welding process, which cannot meet the needs of various components of wind turbines. Summary of the invention
[0004] The object of the present invention is to provide a crack-resistant welding material for a main frame of a nacelle chassis of a wind turbine generator and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis comprises the following steps:
[0007] S1: Mix the alloy powder, composite nano-silicon dioxide and additives, grind, ultrasonically stir, and sieve to obtain a core for later use;
[0008] S2: Take a steel pipe as the outer skin of the welding strip, fill the flux core into the steel pipe, roll and draw it into shape to obtain the welding strip;
[0009] S3: The welding strip is subjected to grinding, polishing, water washing, alkali washing, acid washing, and ultrasonic water washing in sequence to obtain a pre-treated welding strip;
[0010] S4: preparing an electroplating solution containing composite nano-silicon dioxide, placing the pretreated welding strip into the electroplating solution, performing ultrasonic-assisted electroplating treatment, and drying to obtain an anti-cracking welding material for a main frame of a wind turbine cabin chassis.
[0011] Furthermore, the filling rate of the core is 68-78%.
[0012] Furthermore, the auxiliary agent is a compound of sodium fluoride and potassium fluoroaluminate in a mass ratio of 2:1.
[0013] Furthermore, the mass ratio of the alloy powder, the composite nano-silicon dioxide and the additive is 10:2:1.
[0014] Furthermore, the alloy powder is composed of, by weight percentage, 22-32% high carbon ferrochrome powder, 3-6% molybdenum powder, 5-10% CrMnFeCoNi powder, 4-8% titanium carbide powder, 2-5% chromium carbide powder, 6-9% ferroboron powder, and the remainder is reduced iron powder.
[0015] Further, the preparation of composite nano-silicon dioxide comprises the following steps:
[0016] (1) Mix boric acid, propylene glycol and deionized water, add ethyl orthosilicate, add ammonia water, continue stirring, add mannitol aqueous solution, age for 24 hours, heat to 300°C and keep warm for 2-3 hours to obtain boron-doped nano-silica;
[0017] (2) Lanthanum nitrate hexahydrate, yttrium nitrate and N,N-dimethylformamide are mixed, a mixture of terephthalic acid and N,N-dimethylformamide is added, the mixture is transferred into a reaction kettle, the mixture is kept at 108-120°C for 1-2 hours, boron-doped nano-silica is added, the mixture is kept at this temperature for 44-45 hours, the mixture is cooled, filtered, washed and dried to obtain modified nano-silica;
[0018] (3) Mix benzotriazole and ethanol, add modified nano-silica, stir ultrasonically for 1-2 hours, transfer to a vacuum environment, stir ultrasonically for 20-30 minutes, wash and dry to obtain composite nano-silica.
[0019] Furthermore, the working conditions of the ultrasonic assisted electroplating treatment are: current density 4 mA / cm 2 , time is 1h, temperature is 55-60℃, and ultrasonic power is 200W.
[0020] Furthermore, the composition of the electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, which contains 118g / L nickel chloride hexahydrate, 25g / L nickel sulfamate, 17g / L copper chloride dihydrate, and (6-9)g / L composite nano-silica.
[0021] Furthermore, the choline chloride-ethylene glycol ionic liquid is prepared by mixing choline chloride and ethylene glycol in a molar ratio of 1:2.
[0022] Furthermore, the steel pipe is low carbon steel.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a crack-resistant welding material for a main frame of a wind turbine nacelle chassis and a preparation method thereof. By limiting the composition and process, a welding material with good toughness, strong wear resistance, corrosion resistance and good crack resistance is prepared, which can meet the wear and tear repair requirements of the main frame of the wind turbine nacelle chassis.
[0025] The invention mixes alloy powder, composite nano-silicon dioxide and an additive, and obtains a uniformly mixed flux core by ultrasonic stirring. The wear resistance of the deposited metal is synergistically improved by controlling the ratio between the alloy powder, the composite nano-silicon dioxide and the additive in the flux core, and the structure of the weld is densified. The alloy powder is compounded with high-carbon ferrochrome powder, CrMnFeCoNi powder, molybdenum powder, titanium carbide powder, chromium carbide powder, ferroboron powder, reduced iron powder and other components, and high-toughness high-entropy alloy CrMnFeCoNi powder is selected to improve the wear resistance of the flux core. Carbides such as titanium carbide powder and chromium carbide powder are used as reinforcing phases to improve the high-temperature wear resistance of the welding material.
[0026] The addition of composite nano-silica enables the welding material to have a smaller solid-liquid coexistence temperature range during the solidification process, promotes its grain refinement and eutectic silicon morphology change, and improves the welding performance of the welding material; wherein the composite silica is first prepared by a sol-gel method for boron-doped silica, and then a lanthanum and yttrium double rare earth metal skeleton is in situ grown on the boron-doped silica, and then the metal skeleton is used as a nano container of the corrosion inhibitor benzotriazole, thereby greatly improving the uniformity of the dispersion of nano-silica in the core, and a mixture of sodium fluoride and potassium fluoroaluminate is selected as a core additive to reduce the diffuse hydrogen content of the weld metal and improve its crack resistance. The addition of rare earth elements on the composite silica reduces and optimizes the structure and morphology of weld metal inclusions, purifies the weld metal, and further improves its crack resistance; at the same time, because the composite nano-silica contains acid radicals and boron trioxide, it can effectively remove the oxide film on the surface of CrMnFeCoNi, improve its wettability and spreadability, so as to improve the surface hardness, wear resistance and crack resistance of the weld metal.
[0027] In the present invention, a steel pipe is selected as the outer skin of the welding material. In order to improve the rust resistance and corrosion resistance of the welding material and facilitate the storage and use of the welding material, the pretreated welding strip is placed in an electroplating solution containing composite nano-silicon dioxide and ultrasonic-assisted electroplating treatment is performed. In order to meet the existing green production requirements, the present invention selects choline chloride-ethylene glycol ionic liquid as the electroplating solution solvent, and constructs a copper-nickel-composite nano-silicon dioxide layer on its surface, thereby greatly improving the wear resistance and corrosion resistance of the welding material, thereby improving the welding performance of the welding material. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0031] Embodiment 1: A method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis, comprising the following steps:
[0032] S1: Mix the alloy powder, composite nano-silicon dioxide and additives, grind, ultrasonically stir, and sieve to obtain a core for later use;
[0033] The mass ratio of the alloy powder, composite nano-silicon dioxide and additive is 10:2:1;
[0034] The alloy powder is composed of 22% high carbon ferrochrome powder, 5% CrMnFeCoNi powder, 3% molybdenum powder, 4% ferrotitanium powder, 2% chromium carbide powder, 6% ferroboron powder, and the balance is reduced iron powder.
[0035] The auxiliary agent is sodium fluoride and potassium fluoroaluminate in a mass ratio of 2:1;
[0036] The preparation of the composite nano-silicon dioxide comprises the following steps:
[0037] (1) 0.24 g of boric acid, 23 mL of propylene glycol, and 77 mL of deionized water were mixed, 2.5 mL of ethyl orthosilicate and 5 mL of ammonia water were added, stirring was continued, 5 mL of 1 mol / L mannitol aqueous solution was added, the mixture was aged for 24 h, and the temperature was raised to 300 ° C and kept for 2 h to obtain boron-doped nano-silica;
[0038] (2) 1 mmol of lanthanum nitrate hexahydrate, 1 mmol of yttrium nitrate, and 25 mL of N,N-dimethylformamide were mixed, and a mixed solution of 3 mmol of terephthalic acid and 25 mL of N,N-dimethylformamide was added, and the mixture was transferred into a reaction kettle, and kept at 108°C for 2 h, and 2 g of boron-doped nano-silica was added, and the mixture was kept at this temperature for 44 h, and then cooled, filtered, washed, and dried to obtain modified nano-silica;
[0039] (3) Mix 4 g of benzotriazole and 50 mL of ethanol, add 0.5 g of modified nano-silica, stir ultrasonically for 1 h, transfer to a vacuum environment, stir ultrasonically for 20 min, wash and dry to obtain composite nano-silica;
[0040] S2: Take a steel pipe as the outer skin of the welding strip, fill the flux core into the steel pipe, roll, draw and shape it to obtain the welding strip; the filling rate of the flux core is 72%;
[0041] S3: The welding strip is subjected to grinding, polishing, water washing, alkali washing, acid washing, and ultrasonic water washing in sequence to obtain a pre-treated welding strip;
[0042] S4: preparing an electroplating solution containing composite nano-silicon dioxide, placing the pretreated welding strip into the electroplating solution, performing ultrasonic-assisted electroplating treatment, and drying to obtain an anti-cracking welding material for a main frame of a wind turbine nacelle chassis;
[0043] The working conditions of ultrasonic assisted electroplating treatment are: current density 4mA / cm 2 , time is 1h, temperature is 55℃, ultrasonic power is 200W;
[0044] The composition of the electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, which contains 118g / L nickel chloride hexahydrate, 25g / L nickel sulfamate, 17g / L copper chloride dihydrate, and 6g / L composite nano-silicon dioxide;
[0045] The choline chloride-ethylene glycol ionic liquid is prepared by mixing choline chloride and ethylene glycol in a molar ratio of 1:2.
[0046] Embodiment 2: A method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis, comprising the following steps:
[0047] S1: Mix the alloy powder, composite nano-silicon dioxide and additives, grind, ultrasonically stir, and sieve to obtain a core for later use;
[0048] The mass ratio of the alloy powder, composite nano-silicon dioxide and additive is 10:2:1;
[0049] The alloy powder is composed of 27% high carbon ferrochrome powder, 7% CrMnFeCoNi powder, 5% molybdenum powder, 6% ferrotitanium powder, 3% chromium carbide powder, 7% ferroboron powder, and the balance is reduced iron powder.
[0050] The auxiliary agent is sodium fluoride and potassium fluoroaluminate in a mass ratio of 2:1;
[0051] The preparation of the composite nano-silicon dioxide comprises the following steps:
[0052] (1) 0.24 g of boric acid, 23 mL of propylene glycol, and 77 mL of deionized water were mixed, 2.5 mL of ethyl orthosilicate and 5 mL of ammonia water were added, stirring was continued, 5 mL of 1 mol / L mannitol aqueous solution was added, the mixture was aged for 24 h, and the temperature was raised to 300 ° C and kept for 2.5 h to obtain boron-doped nano-silica;
[0053] (2) 1 mmol of lanthanum nitrate hexahydrate, 1 mmol of yttrium nitrate, and 25 mL of N,N-dimethylformamide were mixed, and a mixed solution of 3 mmol of terephthalic acid and 25 mL of N,N-dimethylformamide was added, and the mixture was transferred into a reaction kettle, and kept at 115°C for 1.5 h, and 2 g of boron-doped nano-silica was added, and the mixture was kept at this temperature for 44.5 h, and then cooled, filtered, washed, and dried to obtain modified nano-silica;
[0054] (3) Mix 4 g of benzotriazole and 50 mL of ethanol, add 0.5 g of modified nano-silica, stir ultrasonically for 1.5 h, transfer to a vacuum environment, stir ultrasonically for 25 min, wash and dry to obtain composite nano-silica;
[0055] S2: Take a steel pipe as the outer skin of the welding strip, fill the flux core into the steel pipe, roll, draw and shape it to obtain the welding strip; the filling rate of the flux core is 72%;
[0056] S3: The welding strip is subjected to grinding, polishing, water washing, alkali washing, acid washing, and ultrasonic water washing in sequence to obtain a pre-treated welding strip;
[0057] S4: preparing an electroplating solution containing composite nano-silicon dioxide, placing the pretreated welding strip into the electroplating solution, performing ultrasonic-assisted electroplating treatment, and drying to obtain an anti-cracking welding material for a main frame of a wind turbine nacelle chassis;
[0058] The working conditions of ultrasonic assisted electroplating treatment are: current density 4mA / cm 2 , time is 1h, temperature is 58℃, ultrasonic power is 200W;
[0059] The composition of the electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein there are 118g / L nickel chloride hexahydrate, 25g / L nickel sulfamate, 17g / L copper chloride dihydrate, and 7g / L composite nano-silicon dioxide;
[0060] The choline chloride-ethylene glycol ionic liquid is prepared by mixing choline chloride and ethylene glycol in a molar ratio of 1:2.
[0061] Embodiment 3: A method for preparing a crack-resistant welding material for a main frame of a nacelle chassis of a wind turbine generator comprises the following steps:
[0062] S1: Mix the alloy powder, composite nano-silicon dioxide and additives, grind, ultrasonically stir, and sieve to obtain a core for later use;
[0063] The mass ratio of the alloy powder, composite nano-silicon dioxide and additive is 10:2:1;
[0064] The alloy powder is composed of 32% high carbon ferrochrome powder, 10% CrMnFeCoNi powder, 6% molybdenum powder, 8% ferrotitanium powder, 5% chromium carbide powder, 9% ferroboron powder, and the balance is reduced iron powder.
[0065] The auxiliary agent is sodium fluoride and potassium fluoroaluminate in a mass ratio of 2:1;
[0066] The preparation of the composite nano-silicon dioxide comprises the following steps:
[0067] (1) 0.24 g of boric acid, 23 mL of propylene glycol, and 77 mL of deionized water were mixed, 2.5 mL of ethyl orthosilicate and 5 mL of ammonia water were added, stirring was continued, 5 mL of 1 mol / L mannitol aqueous solution was added, and the mixture was aged for 24 h, and the temperature was raised to 300 ° C and kept for 2-3 h to obtain boron-doped nano-silica;
[0068] (2) 1 mmol of lanthanum nitrate hexahydrate, 1 mmol of yttrium nitrate, and 25 mL of N,N-dimethylformamide were mixed, and a mixed solution of 3 mmol of terephthalic acid and 25 mL of N,N-dimethylformamide was added, and the mixture was transferred into a reaction kettle, and kept at 120°C for 1 hour, and 2 g of boron-doped nano-silica was added, and the mixture was kept at 120°C for 45 hours, and then cooled, filtered, washed, and dried to obtain modified nano-silica;
[0069] (3) Mix 4 g of benzotriazole and 50 mL of ethanol, add 0.5 g of modified nano-silica, stir ultrasonically for 2 h, transfer to a vacuum environment, stir ultrasonically for 30 min, wash and dry to obtain composite nano-silica;
[0070] S2: Take a steel pipe as the outer skin of the welding strip, fill the flux core into the steel pipe, roll, draw and shape it to obtain the welding strip; the filling rate of the flux core is 72%;
[0071] S3: The welding strip is subjected to grinding, polishing, water washing, alkali washing, acid washing, and ultrasonic water washing in sequence to obtain a pre-treated welding strip;
[0072] S4: preparing an electroplating solution containing composite nano-silicon dioxide, placing the pretreated welding strip into the electroplating solution, performing ultrasonic-assisted electroplating treatment, and drying to obtain an anti-cracking welding material for a main frame of a wind turbine nacelle chassis;
[0073] The working conditions of ultrasonic assisted electroplating treatment are: current density 4mA / cm 2 , time is 1h, temperature is 57℃, ultrasonic power is 200W;
[0074] The composition of the electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, which contains 118g / L nickel chloride hexahydrate, 25g / L nickel sulfamate, 17g / L copper chloride dihydrate, and 9g / L composite nano-silicon dioxide;
[0075] The choline chloride-ethylene glycol ionic liquid is prepared by mixing choline chloride and ethylene glycol in a molar ratio of 1:2.
[0076] Comparative Example 1: Example 3 was used as the control group, CrMnFeCoNi powder was not added, and other processes were normal.
[0077] Comparative Example 2: Taking Example 3 as the control group, nano silicon dioxide (S104596: Aladdin reagent) was used to replace the composite nano silicon dioxide, and the other processes were normal.
[0078] Comparative Example 3: Example 3 was used as the control group, and no ultrasonic assisted electroplating treatment was performed, and other processes were normal.
[0079] In the embodiments and comparative examples, the CrMnFeCoNi powder is prepared by compounding Cr powder, Mn powder, Fe powder, Co powder and Ni powder in a mass ratio of 1:1:1:1:1, and the particle size of the CrMnFeCoNi powder is 100 µm.
[0080] Sources of raw materials used (for demonstration purposes only):
[0081] Steel pipe: Its chemical composition is as follows: carbon 0.02%, silicon 0.9%, manganese 2%, chromium 18%, nickel 11%, sulfur 0.01%, and the balance is iron; high carbon ferrochrome powder 20201109: Qinghe County Tebo Metal Materials Co., Ltd.; molybdenum powder AM-Mo-009-1: Zhejiang Yamei Nano Technology Co., Ltd.; titanium iron powder (40 mesh): Alfa Aesar (China) Chemical Co., Ltd.; chromium carbide powder (60 mesh): Beijing Xingrongyuan Technology Co., Ltd.; ferroboron powder (40 mesh): Wuhan Penglei Biotechnology Co., Ltd.; reduced iron powder W00259: Wuhan Jiyesheng Chemical Co., Ltd.; benzotriazole 95-1 4-7: Pandex (Shanghai) International Trading Co., Ltd.; sodium fluoride S111591, potassium fluoroaluminate P190954, ethyl orthosilicate T110593, mannitol M108828, lanthanum nitrate hexahydrate L106046, yttrium nitrate Y106052, N,N-dimethylformamide D111999, terephthalic acid P108506, nickel chloride hexahydrate N112126, nickel aminosulfonate N102822, cupric chloride dihydrate C111678, choline chloride C108896, ethylene glycol E103319: Aladdin reagent; boric acid, glycerol, ammonia water, ethanol, analytical grade: Sinopharm reagent.
[0082] Performance test: The welding materials prepared in the embodiments and comparative examples were tested:
[0083] The prepared welding material was deposited on the surface of 304L stainless steel with a size of 100mm×80mm×12mm. Open arc surfacing was adopted during welding, with a welding current of 200A, a welding voltage of 25V, a welding speed of 10mm / s, and a welding material extension length of 15mm.
[0084] Hardness: tested with a Vickers microhardness tester, with a loading time of 10s and a load of 2N; Wear resistance: the sample was kept at 380℃ for 2h, cooled to 25℃ for wear resistance test, using a vertical universal friction and wear tester, with GCr15 as the grinding material, a turntable speed of 100r / min, a load of 12N, and a wear time of 15min. An electronic balance was used to measure the weight of the sample before and after wear, and the weight of the worn sample ∆G=G0-G1 (G0-weight before wear, G1-weight after wear) was calculated; Corrosion resistance: tested with reference to GB / T1771-2007, with an operating temperature of 37℃, a sodium chloride concentration of 59g / L, and a pH of 7; the results are shown in Table 1;
[0085] Table 1
[0086]
[0087] The present invention provides a crack-resistant welding material for a main frame of a wind turbine nacelle chassis and a preparation method thereof. By limiting the composition and process, a welding material with good toughness, strong wear resistance, corrosion resistance and good crack resistance is prepared, which can meet the wear and tear repair requirements of the main frame of the wind turbine nacelle chassis. The welds of Examples 1-3 are beautiful, and there are no pores or cracks on the surface. In Table 1, / indicates that the item has not been tested.
[0088] By comparing Example 3 with Comparative Example 1, it can be seen that the present invention mixes alloy powder, composite nano-silicon dioxide, and an additive, and ultrasonically stirs to obtain a uniformly mixed flux core, and by controlling the ratio between the alloy powder, composite nano-silicon dioxide, and the additive in the flux core, the wear resistance of the deposited metal is synergistically improved, and the structure of the weld is densified; wherein the alloy powder is compounded with components such as high-carbon ferrochrome powder, CrMnFeCoNi powder, molybdenum powder, titanium carbide powder, chromium carbide powder, ferroboron powder, and reduced iron powder, and high-toughness high-entropy alloy CrMnFeCoNi powder is selected to improve the wear resistance of the flux core, and carbides such as titanium carbide powder and chromium carbide powder are used as reinforcing phases to improve the high-temperature wear resistance of the welding material.
[0089] By comparing Example 3 with Comparative Example 2, it can be seen that the addition of composite nano-silica makes the welding material have a smaller solid-liquid coexistence temperature range during the solidification process, promotes its grain refinement and eutectic silicon morphology change, and improves the welding performance of the welding material; wherein the composite silica is first prepared by a sol-gel method, and then a lanthanum and yttrium double rare earth metal skeleton is in situ grown on the boron-doped silica, and then the metal skeleton is used as a nano-container of the corrosion inhibitor benzotriazole, thereby greatly improving the dispersion of nano-silica in the core. The uniformity is improved, and a mixture of sodium fluoride and potassium fluoroaluminate is selected as a flux core additive to reduce the diffuse hydrogen content of the weld metal and improve its crack resistance. The addition of rare earth elements on the composite silica can reduce and optimize the structure and morphology of weld metal inclusions, purify the weld metal, and further improve its crack resistance. At the same time, because the composite nano-silica contains acid radicals and boron trioxide, it can effectively remove the oxide film on the surface of CrMnFeCoNi and improve its wettability and spreading, so as to improve the surface hardness, wear resistance and crack resistance of the weld metal.
[0090] By comparing Example 3 with Comparative Example 3, it can be seen that in the present invention, a steel pipe is selected as the outer skin of the welding material. In order to improve the rust resistance and corrosion resistance of the welding material and facilitate the storage and use of the welding material, the pretreated welding strip is placed in a plating solution containing composite nano-silicon dioxide and ultrasonic-assisted electroplating treatment is performed. In order to meet the existing green production requirements, choline chloride-ethylene glycol ionic liquid is selected as the electroplating solution solvent in the present invention, and a copper-nickel-composite nano-silicon dioxide layer is constructed on its surface, thereby greatly improving the wear resistance and corrosion resistance of the welding material, thereby improving the welding performance of the welding material.
[0091] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis, characterized in that: The following steps are involved: S1: Mix the alloy powder, composite nano-silicon dioxide and additives, grind, ultrasonically stir, and sieve to obtain a core for later use; S2: Take a steel pipe as the outer skin of the welding strip, fill the flux core into the steel pipe, roll and draw it into shape to obtain the welding strip; S3: The welding strip is subjected to grinding, polishing, water washing, alkali washing, acid washing, and ultrasonic water washing in sequence to obtain a pre-treated welding strip; S4: preparing an electroplating solution containing composite nano-silicon dioxide, placing the pretreated welding strip into the electroplating solution, performing ultrasonic-assisted electroplating treatment, and drying to obtain an anti-cracking welding material for a main frame of a wind turbine nacelle chassis; The auxiliary agent is a compound of sodium fluoride and potassium fluoroaluminate in a mass ratio of 2:1; The mass ratio of the alloy powder, composite nano-silicon dioxide and additive is 10:2:1; The alloy powder is composed of 22-32% high carbon ferrochrome powder, 3-6% molybdenum powder, 5-10% CrMnFeCoNi powder, 4-8% ferrotitanium powder, 2-5% chromium carbide powder, 6-9% ferroboron powder, and the balance is reduced iron powder. The preparation of the composite nano-silicon dioxide comprises the following steps: (1) Boric acid, glycerol and deionized water are mixed, ethyl orthosilicate is added, ammonia water is added, stirring is continued, a mannitol aqueous solution is added, aging is carried out for 24 hours, heating to 300° C. and keeping the temperature for 2-3 hours to obtain boron-doped nano-silica; (2) mixing lanthanum nitrate hexahydrate, yttrium nitrate and N,N-dimethylformamide, adding a mixed solution of terephthalic acid and N,N-dimethylformamide, transferring the mixture into a reaction kettle, keeping the temperature at 108-120° C. for 1-2 hours, adding boron-doped nano-silica, continuing to keep the temperature for 44-45 hours, cooling, filtering, washing and drying to obtain modified nano-silica; (3) Mix benzotriazole and ethanol, add modified nano-silica, stir ultrasonically for 1-2 hours, transfer to a vacuum environment, stir ultrasonically for 20-30 minutes, wash and dry to obtain composite nano-silica.
2. The method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis according to claim 1, characterized in that: The filling rate of the drug core is 68-78%.
3. The method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis according to claim 1, characterized in that: The working conditions of ultrasonic assisted electroplating treatment are: current density 4mA / cm 2 , time is 1h, temperature is 55-60℃, and ultrasonic power is 200W.
4. The method for preparing a crack-resistant welding material for a main frame of a wind turbine nacelle chassis according to claim 1, characterized in that: The composition of the electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, which contains 118g / L nickel chloride hexahydrate, 25g / L nickel sulfamate, 17g / L copper chloride dihydrate, and (6-9)g / L composite nano-silicon dioxide.
5. The method for preparing a crack-resistant welding material for a main frame of a nacelle chassis of a wind turbine according to claim 4, characterized in that: The choline chloride-ethylene glycol ionic liquid is prepared by mixing choline chloride and ethylene glycol in a molar ratio of 1:
2.
6. A crack-resistant welding material for a main frame of a wind turbine nacelle chassis, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Heat-resisting and wear-resisting flux-cored wire
CN105945456A
Chromium carbide enhanced nickel-aluminum-based high-temperature hardfacing flux-cored wire and preparation method
CN112192089A